Building capabilities and territorial resources in mountain tourist areas - Jean-Christophe Dissart (Revue de Géographie Alpine, 2012)
Mass tourism in mountain resorts is facing a number of challenges: climate change, economic crises, increased competition and changing demand. In response to this situation, numerous resorts have embarked on tourism projects, mobilising stakeholders and resources with a view to renewing the tourism product and moving from mass tourism to a form that is more specific. This process is not straightforward, however, and it therefore becomes critical to analyze the conditions that govern the renewal of tourism services in mountain areas. We hypothesize that by using regional generic resources, tourism creates “territorial capabilities” that are then used to build and add value to territorial resources. Tourism, in turn, builds on the latter to adapt. This “virtuous circle” is analyzed in the Oisans region of the Alps. First, we show how tourism has shaped the region by creating conditions for the emergence of territorial capabilities, then we explain how these capabilities enable a renewal of tourism services. Results show that capabilities act as human and social resources for the territory, especially with respect to the development of mountain tourism projects.